Seismically-generated hydroplastic deformation structures in the Late Miocene lacustrine deposits of the Malatya Basin, eastern Turkey - Tasgin, Calibe Koc (Elsevier Science Bv, 2011)
The Late Miocene succession of continental deposits in the Malatya Basin, eastern Anatolia, comprises alluvial-fan, lacustrine and fluvial facies associations. This fault-bounded basin formed in a tectonically active region, notorious for strong earthquakes still today. The lacustrine deposits in the northern part of the basin show several isolated horizons of soft-sediment deformation, including such structures as slump folds, load and flame features, sand dikes and small-scale synsedimentary reverse faults with associated folds. There is no direct evidence supporting instabilities due to unequal loading or overloading, wave-induced cyclical and/or impulsive stresses, sudden changes in groundwater level or bioturbation capable of producing these deformation structures. The soft-sediment deformation structures described in the lacustrine deposits are interpreted as having developed as a result of seismic activity taking place along the Malatya fault zone, based on the tectonic setting of the basin, the lateral extent of the soft-sediment deformation structures over hundreds of metres, their confinement by undeformed layers, the presence of complex structures, and similarities with structures interpreted as being seismically induced in other areas and those obtained experimentally. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Seismites; Lacustrine deposits; Upper Miocene; Malatya Basin; Eastern Anatolia